Tax Legal Remedy Model in Principles of Forming a Sense of Justice Toward the Society - KRISTHY, Mutia Evi; YANDI, Ahmad; SISY; VALINA; MURTI, Jentung Wisnu; SETYONO, Aries; SALAHIDIN; ASIHAY, Yayang (Indonesia Strategic Sustainability, 2024)
Purpose: The source of state revenue comes from community participation. The tax state is one of the ways to collect taxes from its people because taxes are used as a means for the welfare of the people. (SPT), then deposit their tax obligations. The enormous trust of taxpayers in taxpayers is naturally balanced with supervisory instruments; for this purpose, the tax authorities are given the authority to carry out tax audits.Methodology:The type of research that will be used in this proposal is empirical legal research. This type of empirical legal research uses field data, such as the results of interviews and observations, as the primary data source. Empirical legal research is used to analyze the law, seen as patterned social behavior in people's lives that constantly interacts and relates to social aspects.Findings: If the inspection results show discrepancies or discrepancies, the paying tax authorities issue a Tax Assessment Letter (SKP), which functions as a Billing Letter. In practice, there are often differences in settlement between the tax authorities and taxpayers, which is one reason for tax disputes arising.Implication:Within the framework of a rule of law state, the taxpayer is entitled to legal protection to resolve the dispute in case of a tax dispute. The dispute resolution pathways provided include objections, appeals, and lawsuits.